Effect of multiple stressors on the functional traits of sub-tidal macrobenthic fauna: A case study of the southeast coast of India. (February 2022) - Pandey, Vikas; Jha, Dilip Kumar; Kumar, P. Sathish; Santhanakumar, J.; Venkatnarayanan, S.; Prince Prakash Jebakumar, J.; Dharani, G.
Abstract: The use of functional information of taxa is a promising approach to uncover the underlying mechanism of ecosystem functioning. We used biological trait analysis (BTA) to assess the functional response of subtidal macrobenthos with multiple stressors. Seventeen environmental variables from 42 stations of five coastal districts were assessed along the southeast coast of India. Dominant fauna was assigned into 20 categories belonging to six functional traits. Additionally, we used five ecological groups (EG) of AMBI as a covariable trait to validate functional traits and EG relationship. The trait composition in the communities showed significant variation between undisturbed and disturbed areas. RLQ/Fourth corner combined approach illustrated the effects of stressors and isolated the corresponding species associated with different stressors. Smaller, short-lived, deposit-feeding, and discretely motile fauna occurred at the disturbed areas, whereas, larger, long-lived, and highly motile at the undisturbed area. Dissolved oxygen, organic enrichment, and metals concentration were the main environmental descriptors influencing the trait composition. The results highlight the importance of the BTA approach to uncover the response of the macrobenthic community to anthropogenic disturbances-driven impacts in multi-stressed near-shore coastal ecosystems. Highlights: Macrofaunal functional trait response to multiple stressors was analysed. RLQ/Fourth corner method identified the trait-stressor linkage for macrofauna. Trait composition showed clear variation between disturbed & undisturbed areas. A shift from sensitive to opportunistic trait was observed at disturbed sites. The method will be useful for benthic ecological functioning & monitoring purposes.